Tumor Necrosis Factor-α and Interleukin-6: Potential Interorgan Inflammatory Mediators Contributing to Destructive Periodontal Disease in Obesity or Metabolic Syndrome - Roozbeh Khosravi; Khady Ka; Ting Huang; Saeed Khalili; Bich Hong Nguyen; Belinda Nicolau; Simon D. Tran (Mediators of Inflammation)
Obesity has become a worldwide health burden in the last two decades. Obesity has been associated with increased comorbidities, such as coronary artery disease, diabetes, and destructive periodontal disease. Obesity is also part of a group of risk factors occurring together in an individual, which is referred to as metabolic syndrome. Clinical studies have shown higher risk for destructive periodontal disease in obesity and metabolic syndrome. However, the role of obesity and metabolic syndrome in the onset and development of destructive periodontal disease has not yet been fully understood. In this review, we discuss a working model, which focuses on interorgan inflammation as a common etiological factor for destructive periodontal disease associated with obesity and metabolic syndrome. Specifically, we suggest that elevated levels of tumor necrosis factor-α (TNF-α) or interleukin 6 (IL-6)—both adipokines and known risk factors for destructive periodontal disease—in obesity and metabolic syndrome contribute to the onset and development of destructive periodontal disease. The connections between destructive periodontal disease and systemic conditions, such as obesity or metabolic syndrome, are complex and potentially multidirectional. This review largely focuses on TNF-α and IL-6, inflammatory mediators, as potential common risk factors and does not exclude other biological mechanisms.